Evaluasi Pembinaan Program Anak Penyandang Kesejahteraan Sosial di Kampung Anak Negeri Dinas Sosial Kota Surabaya - Talitha Zitha Vasthi; Bambang Kusbandrijo; Supri Hartono (Concept: Journal of Social Humanities and Education, 2024)
Policy program evaluation is a systematic process for evaluating the effectiveness, efficiency, relevance and impact of a government policy or program. The main objective is to understand the extent to which the program or policy has succeeded in achieving its objectives, as well as to identify areas of improvement or adjustments needed. Policy evaluation is a step important in a sustainable public policy cycle, helping to ensure that policies can provide maximum benefits for the community. The State Children's Village is a program designed by the Surabaya City Social Service to provide services and protection to children who are in need and have social problems in their area. Evaluation of the development program for children with social welfare in the Surabaya City Social Service's State Children's Village was carried out comprehensively to ensure the effectiveness and positive impact of the program. The State Children's Village Program is an initiative of the Surabaya City Social Service which aims to provide guidance and assistance to children who suffer from social welfare. need, especially those who are considered recipients of social welfare or have social problems. This program focuses on developing children through training, coaching and mentoring so that they can live better, more humanely, and learn to behave normally. Through a comprehensive evaluation, the coaching program Kampung Anak Negeri can ensure that efforts to develop children in the city of Surabaya really have a significant impact in improving their welfare and creating better conditions for future generations.